(In)voluntary entrepreneurs. A study of tradition usage as a departure for rural entrepreneurship - Fedoseev, Viktor (UiT Norges arktiske universitet, 2018)
People from Kenozerje ceased to be citizens of the Soviet state on December 26, 1991, and two days later received a citizenship of the Kenozersky National Park, a new incredible country stretched on the borders of the Arkhangelsk region in Russia. The Park uses traditions established on its territory as a departure for activities and constructing an everyday life in Kenozerje. The Park is constantly facing the dilemmas – how to preserve local culture and how to involve people into handling and initiating projects in Kenozerje?